2006
DOI: 10.1021/jo0523767
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Oxidation of 2,3-Dimethylhydroquinone in the Presence of 1,3-Dicarbonyl Compounds

Abstract: The electrooxidation of 2,3-dimethylhydroquinone (1) has been studied in the presence of 2-phenyl-1,3-indandione (3a), 3-hydroxy-1H-phenalen-1-one (3b), and 2-chloro-5,5-dimethyl-1,3-cyclohexanedione (3c) as CH acid nucleophiles in water/acetonitrile (85/15) solution, using cyclic voltammetry and controlled-potential coulometry. The results indicate that p-benzoquinone, generated by electrochemically driven oxidation of the 2,3-dimethylhydroquinone (1), is scavenged by 3a-c, to give related products (5a, 9b, 8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(25 citation statements)
references
References 23 publications
2
23
0
Order By: Relevance
“…2 (curve a), a cathodic peak C 1 appeared on the reverse sweep, at 0.26 V vs. SCE, illustrating the partial reversibility of the two-electron transfer that could be assigned to the 2,5-dihydroxybenzoic acid (1a)/p-benzoquinone (3,6-dioxocyclohexa-1,4-dienecarboxylic acid) (2a) redox couple. A peak current ratio ðI C1 p =I A1 p Þ of nearly unity, particularly during the repetitive recycling of potential, can be considered as a criterion for the stability of p-benzoquinone (2a) produced at the surface of the electrode under the experimental conditions [18][19][20]. The oxidation of 2,5-dihydroxybenzoic acid (1a) in the presence of indole (3) as a nucleophile was studied in some details.…”
Section: Resultsmentioning
confidence: 99%
“…2 (curve a), a cathodic peak C 1 appeared on the reverse sweep, at 0.26 V vs. SCE, illustrating the partial reversibility of the two-electron transfer that could be assigned to the 2,5-dihydroxybenzoic acid (1a)/p-benzoquinone (3,6-dioxocyclohexa-1,4-dienecarboxylic acid) (2a) redox couple. A peak current ratio ðI C1 p =I A1 p Þ of nearly unity, particularly during the repetitive recycling of potential, can be considered as a criterion for the stability of p-benzoquinone (2a) produced at the surface of the electrode under the experimental conditions [18][19][20]. The oxidation of 2,5-dihydroxybenzoic acid (1a) in the presence of indole (3) as a nucleophile was studied in some details.…”
Section: Resultsmentioning
confidence: 99%
“…The indenedione derivative (2-(2,5-dihydroxy-3,4-dimethylphenyl)-2-phenyl-2H-indene-1,3-dione), (see Scheme 1 for structure), was synthesized and purified according to the procedure described recently. 38 In the present paper, we refer to this indenedione derivative as indenedione for convenience. Doubly distilled water was used to prepare all the solutions.…”
Section: Reagents and Apparatusmentioning
confidence: 99%
“…2 curve a) [11][12][13][14][15]. The oxidation of 1,4-hydroquinone (1) in the presence of 1,3-cyclopentadiene as a diene was studied in some detail.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, after the first electrochemical study of catechol in the presence of 1,3-cyclopentadiene [10], we now report electrochemical study, electrochemical synthesis and kinetic evaluation of oxidation of 1,4-hydroquinone in the presence of 1,3-cyclopentadiene. Previously we have shown that 1,4-hydroquinone can be oxidized electrochemically to p-benzoquinones and the formed quinone can be attacked as Michael acceptors by a variety of nucleophiles [11][12][13][14][15]. In contrast to our previous works, in this work the electro-generated p-benzoquinone is used as a dienophile.…”
Section: Introductionmentioning
confidence: 84%